Utilization of Zakat for Pandemic Countermeasures - Badrah Uyuni; Celina Balqis; Lia Fitriani; Nova Auliyatul Faizah; Akmaluddin Murdani; Ummi Rosilawati (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2020)
The global pandemic related to Covid-19 that occurred in Indonesia has made humans experience a difficult situation that requires assistance in terms of support, material and financial. And zakat as a source of social funds in Islam has a strategic role to fulfill these needs. This study uses available literature and news developments from various media as the main reference for analysis. Observations by going directly to get involved in collecting zakat were also conducted. The decision of the Minister of Religion Fachrurozi is in accordance with the instructions of Vice President Ma'ruf Amin so that the community can collect zakat massively even though it is not yet due. So that it is expected to play a role as a social safety net for residents affected by Covid-19. The hope is that it can immediately help ease the burden of life, fulfilling the basic needs, and maintain the purchasing power of residents affected by Covid-19. It turns out that this effort creates conducive conditions and attracts public participation to fulfill zakat and increase awareness of others.